2017
DOI: 10.18632/oncotarget.20963
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Miro1 disturbs mitophagy and pancreatic β-cell function interfering insulin release via IRS-Akt-Foxo1 in diabetes

Abstract: Mitochondrial function is essential to meet metabolic demand of pancreatic beta cells respond to high nutrient stress. Mitophagy is an essential component to normal pancreatic β-cell function and has been associated with β-cell failure in Type 2 diabetes (T2D). Our previous studies have indicated that mitochondrial Rho (Miro) GTPase-mediated mitochondrial dysfunction under high nutrient stress leads to NODlike receptor 3 (NLRP3)-dependent proinflammatory responses and subsequent insulin resistance. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…However, recent data suggest that although Miro deletion affects mitochondrial distribution and motility, the mitochondria retain functionality and membrane potential (Nguyen et al , ; López‐Doménech et al , ) indicating that the loss of Miro per se does not cause mitochondrial depolarisation (Fig E), which is one of the major causes of mitochondrial removal. In line with our results, Chen et al () showed recently that loss of Miro1 selectively in pancreatic beta cells inhibited mitophagy in vivo .…”
Section: Discussionsupporting
confidence: 93%
“…However, recent data suggest that although Miro deletion affects mitochondrial distribution and motility, the mitochondria retain functionality and membrane potential (Nguyen et al , ; López‐Doménech et al , ) indicating that the loss of Miro per se does not cause mitochondrial depolarisation (Fig E), which is one of the major causes of mitochondrial removal. In line with our results, Chen et al () showed recently that loss of Miro1 selectively in pancreatic beta cells inhibited mitophagy in vivo .…”
Section: Discussionsupporting
confidence: 93%
“…The role of mitochondria movement in mitophagy of pancreatic β-cells has also been reported. Participation of Miro1, a mitochondrial outer membrane protein mediating the anchoring of kinesin-related protein 5 (KIF5) to mitochondria, in mitophagy of β-cells was reported [62].…”
Section: Mitophagy and Diabetesmentioning
confidence: 99%
“…In obese and T2D patients, the substances secreted by dysfunctional mitochondria into the cytoplasm often serve as DAMPs, which activate the NLRP3 inflammasome. Moreover, a diet rich in fats and glucose induces the production of mitochondrial ROS owing to Miro1-induced effects on mitochondria in pancreatic β cells; these effects consequently cause an NLRP3-induced inflammatory response, thereby impairing insulin production [102,103]. Furthermore, thioredoxin (TRX)-interacting protein (TXNIP) disassociation causes the activation of NLRP3 inflammasomes [104,105].…”
Section: Obesity and T2dmentioning
confidence: 99%